Likuiditas dan Profitabilitas Terhadap Struktur Modal Pada Perusahaan Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia - Azwansyah Habibie (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The purpose of this study was to examine the effect of Liquidity and Profitability on Capital Structure. This study tries to provide empirical evidence regarding the effect of Liquidity and Profitability on Capital Structure. The independent variable in this study is liquidity which is proxied using the Current Ratio and Profitability is proxied using Return on Assets. While the dependent variable in this study is the Capital Structure which is prorated using the Debt to Equity Ratio. The population used for this study were all companies listed on the Indonesian Stock Exchange in the agricultural sector in the period 2017 to 2020. There were 21 companies. The sample used is 32 observations. multiple regression analysis which is processed using SPSS Version 20 program. The results of quantitative analysis show that the Current Ratio (CR) has no effect on the Debt to Equity Ratio (DER). Return on Assets has an effect on the Debt to Equity Ratio based on the t-count value of -0.131 and a significant value of 0.896, so it can be concluded that the hypothesis is rejected